Cultural landscape conservation in the Boyne Valley Archaeological Park, Counties Meath and Louth, Ireland - Stout, Geraldine (Trinity College (Dublin, Ireland). Department of Geography, 2000)
The establishment of the Boyne Valley Archaeological Park in 1987 and its subsequent designation as a World Heritage Property in 1993 were significant steps in landscape conservation in Ireland. For the first time, the state recognised the importance of the cultural content of the landscape (as opposed to the primarily 'natural' landscapes of other National Parks), and the need to conserve it in toto. The designated 'core area' is focused on the Neolithic passage tombs of Newgrange, Knowth and Dowth in an area known as the Bend of the Boyne in eastern county Meath, but it also includes 'buffer zones' extending south of the river and north of the main concentration of tombs. Despite the small size of the designated area (3,300ha), it includes Europe's most important collection of megalithic art, a significant concentration of Bronze Age sites, sites traditionally associated with the origin of St Patrick's Christian mission in Ireland, and the site of the Battle of the Boyne (1690), one of Europe's most significant battles.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin